Kefir: a comprehensive overview of microbiological, physicochemical, and health-promoting properties - OLIVEIRA, Catarina Demarchi de; SAMPAIO, Aryele Nunes da Cruz Encide; CÉZAR, Camila Koutsodontis Cerqueira; CARON, Evelyn Fernanda Flores; MARTINS, Otávio Augusto; POSSEBON, Fabio Sossai; PEREIRA, Juliano Gonçalves (Food Science and Technology, 2025)
Kefir is a naturally carbonated and mildly acidic milk beverage fermented by grains that consist of bacteria and yeast living in a symbiotic relationship. Its unique flavor arises from a blend of lactic acid, ethanol, carbon dioxide, and other compounds produced by the microorganisms within the kefir grains. The microorganisms in kefir are a complex microbial population that varies by geographical region. Kefir is widely acknowledged for its probiotic content, with reported health benefits that include modulation of intestinal microflora, immune system stimulation, and antimicrobial, antineoplastic, hypocholesterolemic, antidiabetic, and antimutagenic effects. It also exhibits β-galactosidase activity and benefits lipid and blood pressure levels. This review focuses on the microbiological aspects, composition, and production of milk kefir, highlighting how its biological properties correlate with the health benefits associated with its consumption.